Severe Psoriasis With Erythrodermic Rash Manifestation: A Case Report - Hemandasani, Ashwin Shanker; Rahmawati, Lita Diah (Journal of Neonatal Surgery, 2025)
Introduction: Severe psoriasis with generalized erythematous rash impacts on disability, disfiguration, mental health, and quality of life. Case presentation: An Indonesian woman, 23 years old, complained of a chronic erythrodermic rash all over her body and scaly skin for two months. In addition, an unpleasant odor fluid oozes out from multiple erythematous rash lesions. The patient had a history of using herbal medicines and baths. The results of the supporting examinations showed increased leukocyte counts, anti-nuclear antibody (ANA) was detected, and a skin biopsy revealed psoriasis vulgaris. The patient received steroid therapy, and along the way, the patient experienced psychological problems while being treated in the hospital. The patient was an outpatient, was evaluated several times, and showed improvement. Discussion: Psoriasis patients receive first-line treatment, and if it is not effective, biologic agent therapy can be considered. Psoriasis follow-up is important because, in its course, psoriasis is closely related to mental health and mortality, which is influenced by comorbidity and low socioeconomic status. Conclusion: Mental health, psoriasis, skin biopsy, steroid.